Exploring the role of morphology in the evolution of Spanish - Rini, Joel (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 1999)
After a brief survey of the perception of morphological change in the standard works of the Hispanic tradition in the 20th century, the author first attempts to refine concepts such as analogy, leveling, blending, contamination, etc. as they have been applied to Spanish. He then revisits difficult problems of Spanish historical grammar and explores the extent to which various types of morphological processes may have operated in a given change. Selected problems are examined in light of abundant textual evidence. Some include: the resistance to change of Sp. dormir 'to sleep', morir 'to die'.